Targeted sequencing with expanded gene profile enables high diagnostic yield in non‐5q‐spinal muscular atrophies. Issue 9 (25th July 2018) - Karakaya, Mert; Storbeck, Markus; Strathmann, Eike A.; Delle Vedove, Andrea; Hölker, Irmgard; Altmueller, Janine; Naghiyeva, Leyla; Schmitz‐Steinkrüger, Lea; Vezyroglou, Katharina; Motameny, Susanne; Alawbathani, Salem; Thiele, Holger; et al.
Abstract: Spinal muscular atrophies (SMAs) are a heterogeneous group of disorders characterized by muscular atrophy, weakness, and hypotonia due to suspected lower motor neuron degeneration (LMND). In a large cohort of 3, 465 individuals suspected with SMA submitted for SMN1 testing to our routine diagnostic laboratory, 48.8% carried a homozygous SMN1 deletion, 2.8% a subtle mutation, and an SMN1 deletion, whereas 48.4% remained undiagnosed. Recently, several other genes implicated in SMA/LMND have been reported. Despite several efforts to establish a diagnostic algorithm for non‐5q‐SMA (SMA without deletion or point mutations in SMN1 [5q13.2]), data from large‐scale studies are not available. We tested the clinical utility of targeted sequencing in non‐5q‐SMA by developing two different gene panels. We first analyzed 30 individuals with a small panel including 62 genes associated with LMND using IonTorrent‐AmpliSeq target enrichment. Then, additional 65 individuals were tested with a broader panel encompassing up to 479 genes implicated in neuromuscular diseases (NMDs) with Agilent‐SureSelect target enrichment. The NMD panel provided a higher diagnostic yield (33%) than the restricted LMND panel (13%). Nondiagnosed cases were further subjected to exome or genome sequencing. Our experience supports the use of gene panels covering a broad disease spectrum for diseases that are highly heterogeneous and clinically difficult to differentiate. Abstract : Of 3465 individuals with suspected spinal muscular atrophy (SMA) tested in routine diagnostic setting, about half failed to show an SMN1 deletion. To identify the genetic cause in these non‐5q‐SMA individuals, two gene panels: a small one with 62 lower motor neuron disease genes and a large one with 479 neuromuscular disease‐related genes were developed. Unsolved cases were further analysed on WES/WGS. Based on our data, we discuss the best strategy for genetic testing of non‐5q‐SMA individuals.